Knowledge combination and sustainability of the Eyre Peninsula's fishing industry in Australia. (17th October 2019) - Quartey, Samuel Howard; Wells, Sam
Abstract: This paper develops a knowledge combination view on sustainable industries by investigating the Eyre Peninsula's fishing industry in Australia. Although the notion of knowledge combination has received great attention, it is less researched at the industry level. Researchers examining knowledge combination have paid less attention to sustainable industries, which this paper seeks to address. After examining the Eyre Peninsula's fishing industry by interviewing 54 different individual actors representing a wide range of sectors within the industry, this study uncovers the following seven distinctive bundles of knowledge that when combined can underpin the sustainability of the industry: sustainability, industrial, intergenerational, institutional, collective, scientific, and technological knowledge. The findings also reveal that different integrating mechanisms supported the combination and integration of the bundles of knowledge towards the sustainability of the Eyre Peninsula's fishing industry. The findings further suggest that the combination of these knowledge explains current improvements in environmental, economic, and social sustainable practices within the industry. The primary contribution of this paper is to introduce and develop a knowledge combination view on sustainable industries and also add to the literature on knowledge‐based view of sustainability. The theoretical, managerial, and research implications of these findings are discussed.